1998
DOI: 10.1111/j.1349-7006.1998.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Sensitivity of Tumor Cells to Bleomycin as an Indicator of Tumor Response to Electrochemotherapy

Abstract: Electrochemotherapy (ECT) involves the use of locally applied electric pulses to increase delivery of chemotherapeutic drugs into cells in tissues. ECT with bleomycin (BLM) is a very effective local treatment, but different tumors have different response rates to ECT. The aim of our study was to compare the responsiveness of SA-1 and EAT tumors to BLM and ECT in vitro and in vivo, in order to find possible reasons for the observed difference in response rate. The difference in sensitivity to ECT in vitro betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 21 publications
3
21
2
2
Order By: Relevance
“…This is consistent with a report of relatively little antivascular action of cisplatin in vivo (Clements et al, 1999). In contrast, the present result for bleomycin indicates that HMEC-1 cells show an equal, or enhanced, sensitivity to that reported for tumour cells with the maximum value of ˜2 00-fold more sensitive than tumour cell lines (Table 2) (Hait et al, 1994;Dirix et al, 1997;Cemazar et al, 1998a). At present, only Dirix et al have reported on the sensitivity of two different endothelial cell lines to bleomycin (Dirix et al, 1997).…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…This is consistent with a report of relatively little antivascular action of cisplatin in vivo (Clements et al, 1999). In contrast, the present result for bleomycin indicates that HMEC-1 cells show an equal, or enhanced, sensitivity to that reported for tumour cells with the maximum value of ˜2 00-fold more sensitive than tumour cell lines (Table 2) (Hait et al, 1994;Dirix et al, 1997;Cemazar et al, 1998a). At present, only Dirix et al have reported on the sensitivity of two different endothelial cell lines to bleomycin (Dirix et al, 1997).…”
Section: Discussioncontrasting
confidence: 40%
“…Increased drug uptake and potentiation of cytotoxicity has been demonstrated in vitro for several tumour cell lines treated with cisplatin, bleomycin, peplomycin and others, following exposure to electric pulses (Orlowski et al, 1988;Sersa et al, 1995;Kambe et al, 1996;Cemazar et al, 1998a;Kuriyama et al, 1999). When used in combination with application of electric pulses the drug dosage can be greatly reduced for equivalent or higher cytotoxic effect, compared to drug treatment alone (Orlowski et al, 1988;Sersa et al, 1995;Kambe et al, 1996;Cemazar et al, 1998a;Kuriyama et al, 1999). When electrochemotherapy is performed in vivo, the tumour perfusion and intravascular concentration of the drug are additional factors to be considered in achieving optimal tumour cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many immunizations are based on the delivery of protein drugs and are often done by injection. Current effort in the area of drug delivery include the development of targeted delivery in which the drug is only active in the target area of the body (for example, in cancerous tissues) and sustained release formulations in which the drug is released over a period of time in a controlled manner from a formulation Cemaẑar et al (1998); ; Serŝa et al (1993). This is achieved by combining phenomenon of electroporation with the application of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The principal mechanism of this therapy is increased permeabilization of cell membranes, resulting in increased binding of the chemotherapeutic drugs to DNA; binding to DNA was increased fourfold for bleomycin and twofold for cisplatin with appropriate electric-field distribution in the tumors (8)(9)(10)(11)(12)(13). Electrochemotherapy is already being used in clinical settings, and the results of published clinical trials have demonstrated that electrochemotherapy has excellent antitumor effects in different cutaneous and subcutaneous tumors, predominantly in palliative care, resulting in approximately 80% objective responses of the treated tumor nodules (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%